The Relationship Between The Consumption of The Local Herbal Drink Sarabba and a Healthy Lifestyle With Menstrual Cycle Regularuty among Adolescent Girls - Mustari, Rohani; Maryam, Andi; Indrawati, Andi; Elis, Andi; Yulianti, Rahmi (Jurnal Midwifery, 2026)
Introduction Irregular menstrual cycles are a common reproductive health problem experienced by adolescent girls and can be influenced by various factors, including hormonal changes, stress, physical activity, dietary patterns, and unhealthy lifestyles. In addition to pharmacological therapy, non-pharmacological approaches based on local wisdom are also widely used, one of which is the traditional herbal drink sarabba, which is believed to have benefits for maintaining overall and reproductive health. This study aimed to analyze the effectiveness of consuming the local sarabba herbal drink combined with the implementation of a healthy lifestyle on menstrual cycles among adolescent girls at SMP Tunas Bangsa.Method This study was an observational analytic study with a case-control design and a total population sampling technique, involving a total of 40 adolescent girls. The case group consisted of adolescent girls with irregular menstrual cycles, while the control group consisted of those with regular menstrual cycles. Data were collected using questionnaires covering sarabba consumption, healthy lifestyle practices, and menstrual cycle characteristics, and were analyzed using the Chi-Square test with the assistance of SPSS software. Result The results showed a significant relationship between sarabba consumption and the implementation of a healthy lifestyle with menstrual cycle regularity among adolescent girls (p < 0.05). Adolescent girls who consumed sarabba and practiced a healthy lifestyle tended to have more regular menstrual cycles. Conclusion This study concludes that the consumption of the local sarabba herbal drink combined with the implementation of a healthy lifestyle has an effect on the menstrual cycle regularity of adolescent girls.